Life Cycle Assessment of Heat Recovery Steam Generator - Razali, Mohamad Amir (IRC, 2017)
Heat recovery steam generator in Universiti Teknologi PETRONAS Gas District Cooling (UTP GDC) plant is used to generate steam to support the demand of steam needed by the steam absorption chiller (SAC). In this project, life cycle assessment was used as a method to calculate the energy used and saving of carbon dioxide emission by the heat recovery steam generator at UTP GDC plant. This project was carried out to develop the life cycle model of the heat recovery steam generator and to evaluate the saving of carbon dioxide emission especially during the operational phase. By using Microsoft Excel, a model was developed based on the gas and steam temperature profile of HRSG to quantify the saving of carbon dioxide emission. Based on life cycle energy use in the HRSG table, approximately 99.67% of the energy used comes from the operational phase. This means that the energy used and carbon dioxide emission during the construction phase (0.13%) and disposal and recycle phase (-0.01%) are negligible. Assumed that the pinch point and approach point was 20°F and 15°F respectively, the steam generated by the heat recovery steam generator was calculated for 25 years which is 2475830532.58 kg theoretically if the heat recovery steam generator use the full load of the exhaust heat from gas turbine which is 950°F. As for the saving of the carbon dioxide emission, the steam generated was converted to electricity per hour which is 166,477,296 kW and the theoretical amount of carbon dioxide saved by the HRSG was 68596969.82 kg of CO2e, while the actual amount of carbon dioxide saved by the HRSG was 4104556 kg CO2e. Even though the comparison is big but the amount of carbon dioxide saved by the HRSG with the actual data is still significant in reducing the amount of CO2 emission to the surroundings. This shows that the usage of HRSG in the plant not only increase the overall plant efficiency but it also helps to reduce the CO2 emission by the gas turbine to the surroundings.